Evaluation of the Articular Disc Using the Magnetic Resonance Cartigram in Asymptomatic and Symptomatic Temporomandibular Disorders - Aparna Sivakumar; Anuradha Ganesan; Krithika Chandrasekar Lakshmi; Yesoda Aniyan; Saravanan Kannan (Indian Journal of Radiology and Imaging)
Objectives The study is aimed to perform magnetic resonance (MR) cartigram of the articular disc in patients with asymptomatic and symptomatic temporomandibular disorders (TMD).